Application of Drill Learning Method through Typing Master Learning to Improve Office Technology Learning Outcomes Keyboarding Techniques - Dita Adelia Muallim (Universitas Negeri Makassar, 2021)
The drill or exercise learning method is a way of teaching that can train dexterity, speed and accuracy with the aim that students can master higher skills than before. The purpose of this study was to determine the increase in learning outcomes of Keyboarding Technique Office Technology in class X OTKP 1 SMK Negeri 1 Bone, Bone Regency, South Sulawesi Province in semester 1 of the 2019/2020 academic year through the application of Inquiry Learning. This research is Classroom Action Research (CAR) which is carried out for at least 2 cycles. The subjects in this study were 20 students of class X OTKP 1 SMK Negeri 1 Bone. Data collection techniques for Student Learning Outcomes with Learning Outcomes Test. Technical data analysis is quantitative data analysis, namely the average test scores of student learning outcomes